Method for determining the location of radio-emitting objects - Zhelyazov, Mihail (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The report examines the current state of methods and algorithms for determining the absolute and relative coordinates of radio emitting objects in single station onboard radar systems.